Analisis Faktor-Faktor yang Mempengaruhi Keberhasilan Studi Mahasiswa di PTKIN Provinsi Jawa Tengah - Nalim Nalim; Heni Lilia Dewi; Muhammad Aris Safii (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to determine the factors that influence academic achievement and student study period. The method used in this research is ex-post facto qualitative research, with a comparative model that compares several similar variables. The sample involved was 398 students from five State Islamic Universities in Central Java. Samples were selected using the random sampling method. Data collection techniques used are observation and documentation. The data obtained were analyzed using one-way ANOVA and multiple linear regression. The results showed that: (a) Only two of the six factors had a significant effect on student achievement, that was gender and the new student’s admission way. (b) There were four of the seven factors that significantly affected the study period, that was gender, type of high school, GPA, and PMB wayway. (c) There was a significant difference in student achievement in terms of the new student’s admission way. The highest academic achievement (GPA) was achieved by students who are accepted through the National Academic Achievement Selection Wayway of State Islamic Religious Colleges with an average of 3.61. d) There was a significant difference in the study period in terms of the wayway for new students. The fastest study period was reached by students who were accepted through the State Islamic Religious College Entrance Examination way with an average of 8.5 semesters. (e) There was a very significant negative correlation (sig. = 0,000) between the GPA and the study period, which means that the higher the student GPA, the faster the study period.